Cost-Effectiveness of Pembrolizumab as First-Line Treatment for PD-L1 Positive NSCLC: A Systematic Review - Muhammad Akbar Ramadhan Munandar; Hendra Priatna Munandar; Liana Herlina (International Medical Journal Corp. Ltd, 2025)
Introduction: For patients with advanced non-small cell lung cancer (NSCLC) without actionable driver mutations, first-line treatment has been revolutionized by immune checkpoint inhibitors (ICIs), particularly pembrolizumab. While pivotal trials demonstrate superior efficacy of pembrolizumab monotherapy in high PD-L1 expressors (TPS ≥50%) and pembrolizumab-chemotherapy combinations in broader populations, real-world effectiveness, long-term outcomes, and economic sustainability require comprehensive evaluation (Addeo et al., 2019; Rodríguez-Abreu et al., 2021). Methods: This systematic review synthesizes evidence from randomized controlled trials (RCTs), real-world observational studies, and economic evaluations. Literature was sourced from databases including PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library up to 2025. Analyses encompass efficacy (overall survival [OS], progression-free survival [PFS]), safety (immune-related adverse events [irAEs]), and cost-effectiveness (incremental cost-effectiveness ratios [ICERs]). Results: Pembrolizumab-based regimens consistently demonstrate superior OS and PFS compared to chemotherapy alone. In KEYNOTE-024, pembrolizumab monotherapy in PD-L1 TPS ≥50% significantly improved median OS (30.0 vs 14.2 months) (Lisberg et al., 2017). KEYNOTE-189 established pembrolizumab-pemetrexed-platinum as standard for non-squamous NSCLC, showing a 51% reduction in risk of death (Rodríguez-Abreu et al., 2021). Real-world studies confirm this efficacy but note variable outcomes in underrepresented subgroups (Verschueren et al., 2023; Yang et al., 2023). Safety profiles are manageable but distinct, with increased irAEs. Economic analyses show pembrolizumab is cost-effective in the US and several European countries at specific willingness-to-pay thresholds, though results are sensitive to drug costs and healthcare system context (Huang et al., 2017; Chouaid et al., 2019; Kuznik et al., 2021). Discussion: The transformative benefit of pembrolizumab is unequivocal, establishing a new therapeutic paradigm. However, challenges remain in optimizing patient selection beyond PD-L1, managing long-term toxicity and financial toxicity, and integrating novel combinations. The discussion delves into efficacy nuances, safety management, economic implications, and future directions including biomarker refinement and dosing strategies. Conclusion: Pembrolizumab, alone or with chemotherapy, is a cornerstone of first-line advanced NSCLC treatment, offering sustained survival benefits. To maximize its value, future efforts must focus on predictive biomarker development, personalized treatment algorithms, cost-containment strategies, and equitable access.